Electrochemical Cell

JP7668957B2Active Publication Date: 2025-04-25NGK CORP
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2024514170
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2022-04-05
Filing Date
2023-02-17
Publication Date
2025-04-25
Estimated Expiration
2043-02-17

AI Technical Summary

Technical Problem

The hydrogen electrode in electrochemical cells deteriorates when exposed to poisonous substances, such as silicon, due to adhesion, leading to a decrease in electrode reaction efficiency.

Method used

The electrochemical cell design includes a hydrogen electrode with a first portion within 8 μm from the surface having lower ionic conductivity than a second portion, which is more than 8 μm from the surface, allowing poisonous substances to be efficiently adsorbed on the first portion and preventing adhesion on the active three-phase interface, thus suppressing electrode deterioration.

Benefits of technology

This configuration effectively suppresses the deterioration of the hydrogen electrode by adsorbing poisonous substances on the first portion, maintaining the integrity and efficiency of the electrode reaction at the active interface.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 00000007_0000
    Figure 00000007_0000
  • Figure 00000008_0000
    Figure 00000008_0000
  • Figure 00000009_0000
    Figure 00000009_0000
Patent Text Reader

Abstract

In the present invention, a fuel battery cell (10) comprises: a hydrogen electrode (2) containing an ion-conducting material that includes cerium; an oxygen electrode (5); and an electrolyte (3). The hydrogen electrode (2) has a first portion (101) that is within 8 μm from a surface (S2) on the side away from the electrolyte (3), and a second portion (102) that is greater than 8 μm from the surface (S2). The ion conductivity of the first portion (101) is lower than the ion conductivity of the second portion (102).
Need to check novelty before this filing date? Find Prior Art

Description

electrochemical cell

[0001] The present invention relates to electrochemical cells.

[0002] A fuel cell is known as an example of an electrochemical cell (see, for example, Patent Document 1). The fuel cell includes a hydrogen electrode, an oxygen electrode, and an electrolyte disposed between the hydrogen electrode and the oxygen electrode. The hydrogen electrode is composed of nickel (Ni), which functions primarily as an electron conductor, and a ceria-based oxide containing a rare earth element as a solid solution, which functions primarily as an oxygen ion conductor. Gadolinium-doped ceria is a typical example of a ceria-based oxide containing a rare earth element as a solid solution.

[0003] JP 2013-241644 A

[0004] If the gas supplied to the hydrogen electrode contains a poisonous substance (such as silicon), the hydrogen electrode will deteriorate due to the adhesion of the poisonous substance.

[0005] An object of the present invention is to provide an electrochemical cell capable of suppressing deterioration of the hydrogen electrode.

[0006] The electrochemical cell according to the present invention comprises a hydrogen electrode containing an ionically conductive material including cerium, an oxygen electrode, and an electrolyte disposed between the hydrogen electrode and the oxygen electrode. The hydrogen electrode has a first portion located within 8 μm of a surface opposite the electrolyte and a second portion located beyond 8 μm from the surface. The ionic conductivity of the first portion is lower than the ionic conductivity of the second portion.

[0007] According to the present invention, it is possible to provide an electrochemical cell capable of suppressing deterioration of the hydrogen electrode.

[0008] 1 is a perspective view of a fuel cell, FIG 2 is a cross-sectional view of the fuel cell, and FIG 3 is an enlarged view of a portion of FIG 2.

[0009] (Fuel Cell 10) A fuel cell 10 will be described as an example of an electrochemical cell. Fig. 1 is a perspective view of the fuel cell 10. Fig. 2 is a cross-sectional view of the fuel cell 10 taken along a gas flow path 21, which will be described later.

[0010] As shown in FIGS. 1 and 2 , the fuel cell 10 includes a support substrate 20 and a plurality of power generating element sections 30 .

[0011] 1, the support substrate 20 is formed in a flat plate shape. In the support substrate 20 according to this embodiment, the dimension in the length direction (x-axis direction) is longer than the dimension in the width direction (y-axis direction), but the dimension in the width direction may be longer than the dimension in the length direction.

[0012] 2 , the support substrate 20 has a first main surface S1 and a second main surface T1. The first main surface S1 and the second main surface T1 face opposite each other in the thickness direction (z-axis direction) of the support substrate 20. The first main surface S1 and the second main surface T1 support each power generation element portion 30.

[0013] The support substrate 20 is made of a porous material that does not have electron conductivity. For example, the support substrate 20 is made of calcia-stabilized zirconia (CSZ). Alternatively, the support substrate 20 may be made of nickel oxide (NiO) and yttria-stabilized zirconia (YSZ), or may be made of nickel oxide (NiO) and yttria-stabilized zirconia (YSZ). 2 O 3 (yttria), or MgO (magnesium oxide) and MgAl 2 O 4 The support substrate 20 may be composed of a magnesia alumina spinel. The porosity of the support substrate 20 may be, for example, 20% or more and 60% or less. In this specification, the porosity is the ratio of the area of ​​the gas phase to the total area of ​​the solid phase and the gas phase when a cross section is observed using a scanning electron microscope (SEM).

[0014] A plurality of gas flow channels 21 are formed inside the support substrate 20. A fuel gas such as hydrogen gas is supplied to each gas flow channel 21. In this embodiment, each gas flow channel 21 extends in the length direction (x-axis direction) within the support substrate 20. Each gas flow channel 21 penetrates the support substrate 20. It is preferable that each gas flow channel 21 be arranged at substantially equal intervals.

[0015] As shown in Fig. 1, the support substrate 20 is covered with a dense layer 22. The dense layer 22 covers the areas of the surface of the support substrate 20 that are not covered by the power generation element sections 30. The dense layer 22 prevents gases diffused within the support substrate 20 from being discharged to the outside. The dense layer 22 may be made of, for example, magnesium oxide (MgO), CaZrO 3 (Calcium Zirconate), Y 2 O 3 (yttria), MgAl 2 O 4 (magnesia alumina spinel), CSZ (calcia stabilized zirconia), YSZ (8YSZ) (yttria stabilized zirconia), LSGM (lanthanum gallate), GDC (gadolinium doped ceria), or LaCrO 3 (lanthanum chromite) or the like. The dense layer 22 is denser than the support substrate 20. The porosity of the dense layer 22 can be, for example, 0% or more and 7% or less.

[0016] 1 , each power generating element unit 30 is supported on the first main surface S1 or the second main surface T1 of the support substrate 20. The number of power generating element units 30 arranged on the first main surface S1 and the number of power generating element units 30 arranged on the second main surface T1 may be the same as or different from each other. Furthermore, the sizes of the power generating element units 30 may be the same as or different from each other.

[0017] The power generation element sections 30 are arranged at intervals along the longitudinal direction (x-axis direction) of the gas flow channel 21. The power generation element sections 30 are electrically connected in series to one another.

[0018] The power generating element section 30 includes a first current collecting section 1 , a hydrogen electrode 2 , an electrolyte 3 , a reaction prevention layer 4 , an oxygen electrode 5 , a second current collecting section 6 , and an interconnector 7 .

[0019] The first current collector 1 is disposed in a recess 23 of the support substrate 20. The first current collector 1 has a first recess 11 and a second recess 12. The hydrogen electrode 2 is disposed in the first recess 11. The interconnector 7 is disposed in the second recess 12.

[0020] The first current collecting portion 1 is made of a porous material having electron conductivity. For example, the first current collecting portion 1 is made of a material such as NiO (nickel oxide) and Y 2 O 3 Alternatively, the first current collecting portion 1 may be made of NiO (nickel oxide) and 8YSZ (yttria-stabilized zirconia), or may be made of NiO (nickel oxide) and CSZ (calcia-stabilized zirconia).

[0021] The porosity of the first current collecting part 1 can be, for example, 10% to 50%. The thickness of the first current collecting part 1 can be, for example, 50 μm to 500 μm.

[0022] The hydrogen electrode 2 is disposed in the first recess 11 of the first current collector 1. A fuel gas is supplied to the hydrogen electrode 2 from a gas flow channel 21 via a support substrate 20 and the first current collector 1. An electrode reaction represented by the following formula (1) occurs in the hydrogen electrode 2: H 2 +O 2- →H 2 O + 2e - …(1)

[0023] The hydrogen electrode 2 is made of a porous material having electronic and ionic conductivity. The hydrogen electrode 2 contains an ionically conductive material including cerium. The porosity of the hydrogen electrode 2 can be, for example, 10% or more and 50% or less. The thickness of the hydrogen electrode 2 can be, for example, more than 8 μm and 30 μm or less. The configuration of the hydrogen electrode 2 will be described later.

[0024] The electrolyte 3 is disposed so as to cover the hydrogen electrode 2. Both ends of the electrolyte 3 in the length direction (x-axis direction) are connected to interconnectors 7, respectively.

[0025] The electrolyte 3 is made of a dense material that has ionic conductivity but not electronic conductivity. The electrolyte 3 is made of, for example, YSZ (8YSZ), LSGM (lanthanum gallate), or the like. The electrolyte 3 is denser than the hydrogen electrode 2. The porosity of the electrolyte 3 can be, for example, 0% or more and 7% or less. The thickness of the electrolyte 3 can be, for example, 3 μm or more and 50 μm or less.

[0026] The reaction prevention layer 4 is disposed on the electrolyte 3. The reaction prevention layer 4 is disposed at a position corresponding to the hydrogen electrode 2 across the electrolyte 3. The reaction prevention layer 4 is provided to prevent the constituent material of the electrolyte 3 from reacting with the constituent material of the oxygen electrode 5 to form a reaction layer with high electrical resistance. The reaction prevention layer 4 can be made of an ion-conductive material. For example, the reaction prevention layer 4 is made of a material such as GDC=(Ce, Gd)O. 2 The reaction prevention layer 4 may be made of gadolinium-doped ceria. The porosity of the reaction prevention layer 4 may be, for example, 0.1% or more and 50% or less. The thickness of the reaction prevention layer 4 may be, for example, 1 μm or more and 50 μm or less.

[0027] The oxygen electrode 5 is disposed on the reaction prevention layer 4. A gas containing oxygen (e.g., air) is supplied to the oxygen electrode 5 via the second current collector 6. At the oxygen electrode 5, an electrode reaction occurs, which is expressed by the following formula (2): (1 / 2)·O 2 +2e - →O 2- …(2)

[0028] The oxygen electrode 5 is made of a porous material having electron conductivity, for example, LSCF=(La, Sr)(Co, Fe)O 3 (lanthanum strontium cobalt ferrite), LSF = (La,Sr)FeO 3 (lanthanum strontium ferrite), LNF = La(Ni,Fe)O 3 (lanthanum nickel ferrite), LSC = (La,Sr)CoO 3 The oxygen electrode 5 may be made of, for example, lanthanum strontium cobaltite (lanthanum strontium cobaltite). The porosity of the oxygen electrode 5 may be, for example, 10% to 50%. The thickness of the oxygen electrode 5 may be, for example, 10 μm to 100 μm.

[0029] The second current collector 6 is connected to the oxygen electrode 5 and the interconnector 7. The second current collector 6 is made of a porous material having electronic conductivity. The second current collector 6 may or may not have oxygen ion conductivity. The second current collector 6 can be made of, for example, LSCF, LSC, Ag (silver), Ag-Pd (silver-palladium alloy), etc. The porosity of the second current collector 6 can be, for example, 25% or more and 50% or less. The thickness of the second current collector 6 can be, for example, 50 μm or more and 500 μm or less.

[0030] The interconnector 7 is disposed in the second recess 12 of the first current collector 1. Both ends of the interconnector 7 in the length direction (x-axis direction) are connected to the electrolyte 3. The interconnector 7 is made of a dense material having electronic conductivity. The interconnector 7 is made of, for example, LaCrO 3 (Lanthanum chromite), (Sr,La)TiO 3 The interconnector 7 may be made of, for example, strontium titanate (strontium titanate). The porosity of the interconnector 7 may be, for example, 0% or more and 7% or less. The thickness of the interconnector 7 may be, for example, 10 μm or more and 100 μm or less.

[0031] (Configuration of the hydrogen electrode 2) Next, the configuration of the hydrogen electrode 2 will be described. Fig. 3 is a partially enlarged view of Fig. 2 .

[0032] As shown in FIG. 3, the hydrogen electrode 2 has a first portion 101 and a second portion 102 .

[0033] The first portion 101 is a region of the hydrogen electrode 2 on the opposite side to the electrolyte 3. Specifically, the first portion 101 is a region of the hydrogen electrode 2 within 8 μm from the surface S2 on the opposite side to the electrolyte 3. Therefore, the thickness of the first portion 101 is 8 μm. In this embodiment, the first portion 101 is connected to the first current collector 1.

[0034] The surface S2 of the hydrogen electrode 2 (i.e., the interface between the first current collector 1 and the hydrogen electrode 2) is identified by a line where the Ce (cerium) content is 3%. The Ce content is obtained by line analysis using an atomic concentration profile, which will be described later.

[0035] The second portion 102 is a region of the hydrogen electrode 2 on the electrolyte 3 side. Specifically, the second portion 102 is a region of the hydrogen electrode 2 that is more than 8 μm from the surface S2. In other words, the second portion 102 is a region of the hydrogen electrode 2 excluding the first portion 101. The second portion 102 is formed integrally with the first portion 101. In this embodiment, the second portion 102 is connected to the electrolyte 3.

[0036] Here, the ionic conductivity of the first portion 101 is lower than that of the second portion 102. That is, the electrode reaction resistance of the first portion 101 is higher than that of the second portion 102. Therefore, during operation of the fuel cell 10, the first portion 101 becomes hotter than the second portion 102 due to the heat of reaction. Therefore, if the fuel gas supplied to the hydrogen electrode 2 contains a poisoning substance (e.g., silicon), the poisoning substance can be efficiently adsorbed onto the first portion 101. This makes it possible to prevent the poisoning substance from adhering to the second portion 102, which constitutes the three-phase interface (reaction field) of the hydrogen electrode 2 where the electrode reaction is active, and therefore, deterioration of the hydrogen electrode 2 (e.g., a decrease in the electrode reaction) can be suppressed.

[0037] The ionic conductivity of the first portion 101 is measured as follows. First, the first portion 101 is determined as a region within 8 μm of the surface S2 on the opposite side of the electrolyte 3 in the cross section of the hydrogen electrode 2 along the thickness direction (z-axis direction). Next, elemental mapping of the first portion 101 is performed using an electron probe micro analyzer (EPMA) to identify the composition and content of each component of the first portion 101. Next, the identified compositions are mixed at the identified content rates and sintered (at 1300°C for 5 hours) to prepare a pellet to be measured. Next, two terminal-mounting pellets made of YSZ are prepared and sintered (at 1300°C for 5 hours). Next, the pellet to be measured is sandwiched between the two terminal-mounting pellets, and a current wire is joined to the terminal-mounting pellet with platinum paste, and a potential wire is joined to the pellet to be measured with platinum paste. Next, the ionic conductivity of the pellet to be measured is measured using a four-terminal method. The ionic conductivity of the pellet to be measured in this manner is the ionic conductivity of the first portion 101 .

[0038] The ionic conductivity of the second portion 102 is measured in the same manner as the ionic conductivity of the first portion 101 .

[0039] The first portion 101 and the second portion 102 each contain an ion-conductive material including Ce (cerium) and Ni (nickel). The ion conductivity of the ion-conductive material contained in the first portion 101 may be lower than the ion conductivity of the ion-conductive material contained in the second portion 102.

[0040] The ion-conductive material contained in the first portion 101 is Y 2 O 3 (yttria), CeO 2 (ceria) and Gd 2 O 3 (gadolinium) solid solution (hereinafter referred to as "Y(Ce, Gd) solid solution"), 2 O 3 , CeO 2 and Sm 2 O 3 (Samaria) solid solution (hereinafter referred to as "Y(Ce, Sm) solid solution"). When the first portion 101 contains a Y(Ce, Gd) solid solution, Y 2 O 3 Since the difference in thermal expansion coefficient between the first portion 101 and the first current collecting portion 1 containing Y can be reduced, it is possible to suppress the occurrence of cracks near the interface between the first portion 101 and the first current collecting portion 1 due to the difference in thermal expansion coefficient. Therefore, a Y(Ce, Gd) solid solution is suitable as the ion-conductive material contained in the first portion 101. The Y(Ce, Gd) solid solution is a Y(Ce, Gd) solid solution containing Y 2 O 3 , CeO 2 and Gd 2 O 3 are dissolved in each other and form a uniform solid phase.

[0041] Examples of the ion-conductive material contained in the second portion 102 include ceria-based oxides doped with rare earth elements. When the second portion 102 contains ceria-based oxides doped with rare earth elements, the reaction resistance of the hydrogen electrode 2 can be reduced due to high ionic and electronic conductivity. Therefore, ceria-based oxides doped with rare earth elements are suitable as the ion-conductive material contained in the second portion 102. Examples of ceria-based oxides doped with rare earth elements include, but are not limited to, gadolinium-doped ceria (GDC), samarium-doped ceria (SDC), and yttrium-doped ceria (YDC). GDC is CeO doped with 5 mol % to 20 mol % of Gd (gadolinium) oxide. 2 (ceria) can be used.

[0042] The ionic conductivity of the first portion 101 can be adjusted by the composition and content of the ion conductive material contained in the first portion 101. The content of the ion conductive material containing Ce in the first portion 101 can be 35 mol % or more and 65 mol % or less.

[0043] The ionic conductivity of the second portion 102 can be adjusted by the composition and content of the ion-conductive material contained in the second portion 102. The content of the ion-conductive material containing Ce in the second portion 102 can be 35 mol % or more and 65 mol % or less.

[0044] The content of the ion-conductive material containing Ce in the first portion 101 and the second portion 102 is obtained by line analysis using an atomic concentration profile, i.e., element mapping using EPMA. Specifically, in a cross section along the thickness direction (z-axis direction in FIG. 3 ), line analysis is performed in the z-axis direction using EPMA to obtain concentration distribution data for each element. Note that EPMA is a concept that includes EDS (Energy Dispersive x-ray spectroscopy).

[0045] The Ni content in the first portion 101 may be 35 mol % or more and 65 mol % or less, and the Ni content in the second portion 102 may be 35 mol % or more and 65 mol % or less.

[0046] The Ni content in the first portion 101 and the second portion 102 is obtained by line analysis using the atomic concentration profile described above. Ni is preferably present as metallic Ni in a reducing atmosphere to which a fuel gas is supplied, but may be present as NiO when no fuel gas is supplied.

[0047] (Modifications of the Embodiment) Although the embodiment of the present invention has been described above, the present invention is not limited to these, and various modifications are possible without departing from the spirit of the present invention.

[0048] [Modification 1] In the above embodiment, a so-called horizontal stripe type fuel cell has been described as an example of a fuel cell, but the electrochemical cell is not limited to this. The present invention can also be applied to an electrochemical cell in which a hydrogen electrode and an oxygen electrode are arranged on either side of an electrolyte layer.

[0049] An electrochemical cell is a general term for an element in which a pair of electrodes is arranged so that an electromotive force is generated from an overall oxidation-reduction reaction in order to convert electrical energy into chemical energy, and an element for converting chemical energy into electrical energy.

[0050] Examples of electrochemical cells include horizontally striped fuel cells, vertically striped fuel cells, flat plate fuel cells, cylindrical fuel cells, and electrolysis cells that generate hydrogen by utilizing the electrolysis reaction of water. 2- (oxygen ion) was used as the carrier, but OH - (hydroxide ions) or protons may be used as carriers.

[0051] [Modification 2] In the above embodiment, the power generating element section 30 is provided with the reaction prevention layer 4, but it does not have to be provided with the reaction prevention layer 4.

[0052] REFERENCE SIGNS LIST 10 fuel cell 20 support substrate 30 power generating element section 1 first current collecting section 2 hydrogen electrode 101 first section 102 second section 3 electrolyte 4 reaction prevention layer 5 oxygen electrode 6 second current collecting section 7 interconnector

Claims

1. An electrochemical cell comprising: a hydrogen electrode containing an ionically conductive material including cerium; an oxygen electrode; and an electrolyte disposed between the hydrogen electrode and the oxygen electrode, wherein the hydrogen electrode has a first portion located within 8 μm of a surface opposite the electrolyte and a second portion located more than 8 μm from the surface, and the ionic conductivity of the first portion is lower than the ionic conductivity of the second portion.

2. The electrochemical cell of claim 1, wherein the first portion contains a solid solution of yttria, ceria, and gadolinia, and the second portion contains a ceria-based oxide doped with a rare earth element.